Kajian Kastrasi Dalam Novel “Sebuah Harga Untuk Percaya” Karya Tere Liye - Maguna Eliastuti; Roni Sianturi; Cahya Sanjaya Amarsuta; Nurma Damayanti (Universitas Maritim AMNI Semarang, 2023)
The novel “A Price to Believe” by Tere Liye tells that at first the character Jim had the belief since childhood that there was only one true love in life. The feeling of affection for a special woman in his life makes Jim afraid of losing. The novel study uses a castration approach which is useful for knowing the meanings in this study. The purpose of this research journal is to find out about the castration approach. This research method is to describe the novel “A Price to Believe” using qualitative methods. In addition, readers can find out the uniqueness in the study of the castration approach.